PERCEIVED EFFECTIVENESS OF FARMER PRODUCER ORGANISATIONS (FPOS) IN SOCIO-ECONOMIC UPLIFTMENT OF MEMBER FARMERS IN MAHARASHTRA: PERCEIVED EFFECTIVENESS OF FPOS IN SOCIO-ECONOMIC UPLIFTMENT OF MEMBER FARMERS - DERE AISHWARYA; BABITA KUMAR; RAKESH RATHORE (The Journal of Research ANGRAU, 2026)
This paper aims to study the effectiveness of Farmer Producer Organisations(FPOs) in the socio-economic upliftment of member farmers in Maharashtra as perceived by them. FPOs from three districts of Maharashtra were selected. All member farmers from 30 FPOs were selected as the population for the study. From each FPO, 10 farmer members were selected. A list of member farmers was obtained from each FPO based on their convenience, availability, and willingness to respond. Primary data was collected through a pre-structured and pre-tested questionnaire. Mean, percentage, one-sample t-test, were used for the analysis of collected data. Results of the study revealed that farmer members were aware of the business plan of FPOs (5.00), followed by awareness regarding the working of FPOs (3.72). Member farmers join FPO to get a better price for produce (5.00), enhance their income (5.00), and save on input cost (4.35). FPOs have enhanced their income by better realization for their produce (4.62), followed by FPO facilitating the availability of extension services (4.53). Member farmers were satisfied with FPOs business operations such as transparency in business operations (4.45) and enhancement in income on account of joining FPOs (4.41). The major reason to join the FPO was to increase the income, avoids involvement of middlemen and save input cost for the farmer members.